Clinical interventions to reduce stillbirths in sub‐Saharan Africa: a mathematical model to estimate the potential reduction of stillbirths associated with specific obstetric conditions. (5th October 2016) - Goldenberg, RL; Griffin, JB; Kamath‐Rayne, BD; Harrison, M; Rouse, DJ; Moran, K; Hepler, B; Jobe, AH; McClure, EM
Abstract : Objective: Stillbirths are among the most common adverse pregnancy outcomes, with 98% occurring in low‐income countries. More than one‐third occur in sub‐Saharan Africa (SSA). However, the medical conditions causing stillbirths and interventions to reduce stillbirths from these conditions are not well documented. We estimated the reductions in stillbirths possible with combinations of interventions. Design: We developed a computerised model to estimate the impact of various interventions on stillbirths caused by the most common conditions. The model considered the location of obstetric care (home, clinic or hospital) and each intervention's efficacy, penetration and utilisation. Maternal transfers were also considered. Setting and population: Pregnancies in SSA in 2012. Methods: For each condition, we created a series of scenarios involving different combinations of interventions and modelled their impact on stillbirth rates. Main outcome measures: Stillbirths associated with various maternal and fetal conditions and the percentage reduction with various interventions. Results: Eight to ten maternal and fetal conditions were responsible for most stillbirths, but none for more than 15%. The most common conditions causing stillbirths in SSA include obstructed labour and uterine rupture, fetal distress and umbilical cord complications, fetal growth restriction, pre‐eclampsia/eclampsia, and placental abruption/placenta praevia. Syphilis and malaria contribute smaller numbers. Reducing stillbirths requires appropriate diagnosis and management of each condition, usually including hospital care for monitoring and delivery, often by caesarean section. Maternal syphilis and malaria were the only conditions for which outpatient management alone reduced stillbirth. Conclusions: Most stillbirths in low‐income countries occur at term and during labour and therefore are preventable by appropriate obstetric care. Management focused on the maternal and fetal conditions that cause stillbirths is necessary to achieve stillbirth rates approaching those found in high‐income countries. Tweetable abstract: Reducing stillbirth incidence requires appropriate management of each causative condition and often caesarean delivery. Tweetable abstract: Reducing stillbirth incidence requires appropriate management of each causative condition and often caesarean delivery.